New insights into bacterial Zn homeostasis and molecular architecture of the metal resistome in soil polluted with nano zinc oxide - Dinesh Raghavan; Sreena Chuvatte Patinharekkara; Sheeja Thotten Elampilay; Vijesh Kumar Illathidath Payatatti; Sona Charles; Srinivasan Veeraraghavan; Jayarajan Kadiyalath; Sajith Vandana; Subila Kizhakke Purayil; Haritha Prasadam; Shalini Jayaraj Anitha (Ecotoxicology and Environmental Safety, 2023)
Accumulation of nano ZnO (nZnO) in soils could be toxic to bacterial communities through disruption of Zn homeostasis. Under such conditions, bacterial communities strive to maintain cellular Zn levels by accentuation of appropriate cellular machinery. In this study, soil was exposed to a gradient (50–1000 mg Zn kg-1) of nZnO for evaluating their effects on genes involved in Zn homeostasis (ZHG). The responses were compared with similar levels of its bulk counterpart (bZnO). It was observed that ZnO (as nZnO or bZnO) induced a plethora of influx and efflux transporters as well as metallothioneins (MTs) and metallochaperones mediated by an array of Zn sensitive regulatory proteins. Major influx system identified was the ZnuABC transporter, while important efflux transporters identified were CzcCBA, ZntA, YiiP and the major regulator was Zur. The response of communities was dose- dependent at lower concentrations (<500 mg Zn kg-1 as nZnO or bZnO). However, at 1000 mg Zn kg-1, a size-dependent threshold of gene/gene family abundances was evident. Under nZnO, a poor adaptation to toxicity induced anaerobic conditions due to deployment of major influx and secondary detoxifying systems as well as poor chelation of free Zn ions was evident. Moreover, Zn homeostasis related link with biofilm formation and virulence were accentuated under nZnO than bZnO. While these findings were verified by PCoA and Procrustes analysis, Network analysis and taxa vs ZHG associations also substantiated that a stronger Zn shunting mechanism was induced under nZnO due to higher toxicity. Molecular crosstalks with systems governing Cu and Fe homeostasis were also evident. Expression analysis of important resistance genes by qRT-PCR showed good alignment with the predictive metagenome data, thereby validating our findings. From the study it was evident that the induction of detoxifying and resistant genes was greatly lowered under nZnO, which markedly hampered Zn homeostasis among the soil bacterial communities.